Critical Role of Gut Microbiota and Epigenetic Factors in the Pathogenesis of Behçet’s Disease - Ma, Xiaomin; Wang, Xin; Zheng, Guangbing; Tan, Guiqin; Zhou, Fangyu; Wei, Wenwen; Tian, Dan; Yu, Hongsong (Frontiers in Cell and Developmental Biology, 2021)
Behçet’s disease (BD) is a chronic refractory multisystem autoimmune disease, characterized by typical clinical features of nonspecific vasculitis, oral and genital ulcers, uveitis, as well as skin lesions. The exact etiopathogenesis of BD remains unknown, existing studies have indicated that genetics and environmental factors contribute to the increased development of BD. Recently, several studies have shown that external environmental factors can affect the process of epigenetic modification, and abnormalities of epigenetic factors have been confirmed to be involved in the occurrence of BD. At the same time, abnormalities of gut microbiota (GM) in the body, have also been confirmed to participate in the pathogenesis of BD by regulating the balance of Th17/Tregs. This article reviews the pathogenesis of BD and summarizes numerous clinical studies, focusing on the mechanism of GM and epigenetic factors impacting on BD, and providing new ideas for further elucidating the pathogenesis of BD.